The study of demographic profile of patients of senile mature cataract attending the eye OPD of GMC Jammu, India - Raina, Bhavani; Sharma, Pallavi (International Journal of Research in Medical Sciences, 2020)
Background: Age related cataract also called as senile cataract is the commonest type of acquired cataract affecting people over the age of 50 years. In developing countries like India, many times patients with cataract report to the hospitals very late, when it has become mature. Keeping this in mind this study was undertaken to study the demographic profile of patients of senile mature cataract attending the OPD of GMC Jammu and to see if there is correlation between demographic factors and time of seeking medical attention. Methods: This study was conducted on 41 patients of senile mature cataract who attended OPD of GMC Jammu from August 2019 to November 2019. All patients were subjected to detailed history taking and ocular examination. Socio-economic status and education level of all patients was assessed. All patients were admitted and underwent cataract surgery with IOL implantation. Results: In study the mean age of patients was 62.46 years with 58.53% patients being females. Majority of patients were from rural background with low socio-economic status and low education levels. Conclusions: From this study we concluded that female sex, low socio-economic status, comorbidities and lower literacy levels are associated with patients seeking medical attention for cataract at an advanced stage.